Endogenous and microbial biomarkers for periodontitis and type 2 diabetes mellitus - Li, Songjun; Li, Hongwen; Kong, Haiying; Wu, Shang Ying; Cheng, Chak Kwong; Xu, Jian (Frontiers in Endocrinology, 2023)
It has been well documented that there is a two-way relationship between diabetes mellitus and periodontitis. Diabetes mellitus represents an established risk factor for chronic periodontitis. Conversely, chronic periodontitis adversely modulates serum glucose levels in diabetic patients. Activated immune and inflammatory responses are noted during diabetes and periodontitis, under the modulation of similar biological mediators. These activated responses result in increased activity of certain immuneinflammatory mediators including adipokines and microRNAs in diabetic patients with periodontal disease. Notably, certain microbes in the oral cavity were identified to be involved in the occurrence of diabetes and periodontitis. In other words, these immuneinflammatory mediators and microbes may potentially serve as biomarkers for risk assessment and therapy selection in diabetes and periodontitis. In this review, we briefly provide an updated overview on different potential biomarkers, providing novel diagnostic and therapeutic insights on periodontal complications and diabetes mellitus. *Red color: body fluids or tissues/cells where these biomarkers could be collected for potential diagnostic purpose.